SAT0001 Cryopyrin Associated Periodic Syndromes (CAPS): Investigations on Knock-In Mouse Model to Exploit Novel Approaches for the Modulation of the NLRP3 Inflammasome. (9th June 2015) - Bertoni, A.; Carta, S.; Balza, E.; Castellani, P.; Pellecchia, C.; Penco, F.; Schena, F.; Borghini, S.; Trotta, M.L.; Pastorino, C.; Ceccherini, I.; Martini, A.; et al.
Abstract : Background: CAPS are autoinflammatory diseases characterized by recurrent episodes of fever and systemic inflammation. Three nosological entities representing different phenotypes, from the milder to the most severe (FCAS, MWS, CINCA). Cryopyrin, renamed NLRP3, is part of the intracellular multiprotein complex inflammasome that mediates IL-1 processing and secretion through caspase-1 activation. NLRP3 mutations in CAPS are gain-of-function, as they enhance inflammasome activity. The result is hypersecretion of IL-1, responsible for the inflammatory clinical manifestations. Objectives: – To increase the knowledge on the pathologic consequences of NLRP3 mutations in CAPS patients; – To understand the underlying molecular and regulatory mechanisms of CAPS disease; – To identify novel molecular targets for the treatment of cryopyrin/NLRP3 related disorders. Methods: We have generated a KI mouse carrying the N475K mutation into the murine NLRP3 gene. This mutation corresponds to the N477K human mutation, associated to a severe CINCA phenotype with neurological complications; Phenotypical and immunological characterization of NLRP3 Knock In (KI) mice has been performed by flow cytometry; The IL1β secretion from bone marrow derived dendritic cells (BMDCs) and peritoneal macrophages (PMs) of NLRP3 Knock In Mice has been evaluated by ELISA. Results: The NLRP3 KI mice that we have obtained show hair loss, presence of skin rash and reduced survival time when compared to wild type (WT). Autopsy of KI mice, prematurely dead, revealed splenomegaly and a relevant inflammatory status. We compared the IL-1 secretion of inflammatory cells from WT and KI mice. PMs and BMDCs from mutant mice did not secrete mature IL-1β spontaneously. When stimulated with 100 ng/ml of LPS KI cells secreted higher levels of IL-1b than WT cells. The kinetics of IL-1β secretion was much faster in KI cells, reaching the plateau at 3h from exposure to LPS, thus reproducing the results obtained from monocytes of CAPS patients. As in CAPS monocytes, brief exposure to ATP strongly induced the secretion of IL-1β by LPS-activated WT cells while failed to stimulate further IL-1β secretion by inflammatory cells of KI mice. Finally, PMs and BMDCs from KI are more responsive to agonists of TLRs when compared to WT cells: LPS at 0.01 ng/ml triggered high levels of IL-1β secretion (comparable to 100 ng/ml of LPS) in inflammatory cells from KI indicating that the presence of the mutation lowers the threshold of activation. The neurological studies by MRI are in progress Conclusions: The NLRP3 KI mice recapitulates phenotype and functional characteristics of CAPS patients. Thus, this model will hopefully provide elucidations in the mechanisms underlying CAPS as well as other inflammasomepathies. References: Brydges SD et al., Immunity. 2009. Meng et al., Immunity 2009. Gattorno M. et al., Arthritis Rheum. 2013. Disclosure of Interest: None declared